The Emergence and Evolution of the Idea of Discharge or Modification of Contract due to Supervening Events - Dudaš, Atila (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
In this paper the author gives an overview of the emergence and evolution of the idea of discharge or modification of contract due to supervening events, from Roman to contemporary law, with special emphasis on the evolution of the doctrine and its development as a legal institution in the European legislation or case law. The institution of changed circumstances (supervening events) allows the discharge or (judicial) modification of a contract in a situation when the performance of an obligation has not become impossible, but it would require unreasonable costs or the performance would be inexpedient, hence it is considered one of the most striking exceptions to the principle of pacta sunt servanda. It belongs to the group of a very few institutions in relation to which one cannot claim to have direct and clear roots in Roman law. In the works of learned lawyers one may find only sporadic traces of it. In contrast to Roman legal science, Roman philosophy was more favourable to the theory of supervening events, a fact very well proven by the works of Cicero and Seneca. In the late Middle Ages the canonists and, especially, postglossators gave the greatest contribution to the evolution of the theory of supervening events. The school of postglossators considered supervening events a general legal institution, tacitly implied in every legal statement constituting obligation. The ideas of postglossators left a great impact on further evolution of the theory. Even the designation of the institution, clausula rebus sic stantibus, generally accepted in contemporary literature, derives from them. In the period following the postglossators’ time, lasting until the end of the 18th century, there is still an interest in the theory of supervening events in literature. However, under the influence of the school of natural law a somewhat restrictive approach is adopted, in the German doctrine in the first place, according to which the clausula rebus sic stantibus should not be implied in all contracts, but applied exceptionally, if specific conditions are met. The first European civil codes, the Bavarian, Prussian and Austrian, do regulate the effect of supervening events explicitly, in content which is, in general, in line with these theoretical standpoints. It seems that in the 19th century legal science nearly abandoned the idea of supervening events, which could be considered as a consequence of the inviolable primacy of the tenet of pacta sunt servanda, at the time. In line with that, the most important civil codes of this era, such as the French, German and Swiss did not govern the effect of supervening events as a general legal institution. The institution of supervening events is gradually accepted in the case law after the First World War, while the period after the Second World War is heralded by the tendency of its statutory regulation. The ever-growing number of states that regulated supervening events as a general legal institution of contract law included the former Socialist Federative Republic of Yugoslavia, too, as well as the Republic of Serbia and the other states that were once members of the common, South Slavic federal state.